PAJAK DALAM PERSPEKTIF ISLAM: KONSEP, IMPLEMENTASI, DAN RELEVANSI DALAM SISTEM EKONOMI MODERN - Faisal Amri; Ainun Jariyah; Septia Dwi Nurul Aini; dan Hayati Nufus (STKIP Subang, 2025)
This study examines the concept of taxation from an Islamic perspective, its implementation in contemporary economic systems, and its relevance to modern economic principles. Through a literature review approach, this article analyzes the Sharia principles of taxation, the differences between tax and zakat in Islam, and how modern Muslim countries integrate Islamic principles into their tax systems. The results show that Islam has a comprehensive concept of taxation through the instruments of zakat, jizyah, kharaj, and ushr, which aim not only to collect state revenue but also to achieve social justice and equitable distribution of wealth. The implementation of taxation from an Islamic perspective prioritizes the principles of justice (al-'adalah), transparency (al-amanah), and general welfare (maslahah ammah). This study determines that the Islamic taxation system has significant relevance to the modern economic system, particularly in terms of tax progressivity, avoidance of harm, and orientation towards social welfare. This research contributes to a deeper understanding of how Islamic principles can be integrated into modern tax systems to achieve sustainable economic development and justice.